The Brabant study: design of a large prospective perinatal cohort study among pregnant women investigating obstetric outcome from a biopsychosocial perspective. Issue 10 (27th October 2020) - Meems, Margreet; Hulsbosch, Lianne; Riem, Madelon; Meyers, Christina; Pronk, Tila; Broeren, Maarten; Nabbe, Karin; Oei, Guid; Bogaerts, Stefan; Pop, Victor
Abstract : Background: Pregnancy is characterised by many biological and psychosocial changes. Adequate maternal thyroid function is important for the developing fetus throughout gestation. Latent class analyses recently showed three different patterns of change in thyroid function throughout pregnancy with different associations with obstetric outcome. Maternal distress during the pregnancy (anxiety and depression) negatively affects obstetric outcome. Pregnancy distress in turn may be affected by personality traits and attachment styles. Moreover, during the pregnancy, substantial social changes occur in the partner relationship and work experience. The aim of the Brabant study is to investigate the association between thyroid function trajectories and obstetric outcomes. Moreover, within the Brabant study, we will investigate how different trajectories of pregnancy distress are related to obstetric outcome, and the role of personality in this association. We will evaluate the possible role of maternal distress and attachment style on maternal–fetal bonding. Finally, we will study social changes in the perinatal period regarding partner relationship and well-being and performance at work. Methods and analysis: The Brabant study is a longitudinal, prospective cohort study of an anticipated 4000 pregnant women. Women will be recruited at 8–10 weeks gestation among community midwife practices in South-East Brabant in the Netherlands. Thyroid function parameters (TSH and fT4), thyroid peroxidase antibody and human chorionic gonadotrophin will be assessed at 12, 20 and 28 weeks gestation. Moreover, at these three time points women will fill out questionnaires assessing demographic and obstetric features, life style habits and psychological and social variables, such as depressive symptoms, personality, partner relationship quality and burnout. Data from the obstetric records will also be collected. Ethics and dissemination: The study has been approved by the Medical Ethical Committee of the Máxima Medical Center Veldhoven. Results will be submitted to peer-reviewed journals in the relevant fields and presented on national and international conferences.